2022
DOI: 10.7759/cureus.23115
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Pregnancy Complications With Maternal Biochemical Markers Used in Down Syndrome Screening

Abstract: Objective: To determine whether first-and second-trimester maternal serum biomarkers are useful for the prediction of pregnancy complications like preterm birth, intrauterine growth restriction (IUGR), and macrosomia.Methods: We conducted a retrospective analysis of 353 women having first-or second-trimester combined test for Down syndrome screening who delivered at our institution between January 2018 and December 2020. Associations between first-and second-trimester serum markers and adverse pregnancy outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
2
0
3
Order By: Relevance
“…In these studies, no adjustments were made for smoking and maternal weight 9 . In another study 1622 pregnant women who were in IUGR and examined the levels of PAPP-A, free β-hCG, and fetal NT between the groups, and they found that only the PAPP-A level was 3.3 times significant in detecting IUGR below 0.50 MoM 10 . In the group with IUGR, PAPP-A was successful in predicting IUGR with an odds ratio (OR) value of 5.4, a sensitivity of 3.3%, specificity of 99.3%, and a positive predictive value (PPV) of 24.1%, below 0.29 MoM, which is the 1st MoM.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, no adjustments were made for smoking and maternal weight 9 . In another study 1622 pregnant women who were in IUGR and examined the levels of PAPP-A, free β-hCG, and fetal NT between the groups, and they found that only the PAPP-A level was 3.3 times significant in detecting IUGR below 0.50 MoM 10 . In the group with IUGR, PAPP-A was successful in predicting IUGR with an odds ratio (OR) value of 5.4, a sensitivity of 3.3%, specificity of 99.3%, and a positive predictive value (PPV) of 24.1%, below 0.29 MoM, which is the 1st MoM.…”
Section: Discussionmentioning
confidence: 99%
“…Estos marcadores serológicos se combinaron con la prueba de translucencia nucal fetal (NT) y dieron lugar a las pruebas triples y cuádruples. Varios estudios han demostrado que estas pruebas tienen una alta tasa de detección, alrededor del 80% al 90% para trisomía 21 en el primer trimestre del embarazo, con alrededor del 5 % de falsos positivos (9,13).…”
Section: Discussionunclassified
“…A partir de la semana 12, los niveles de beta β-hCG se equilibran y alcanzan concentraciones de 1 MoM en embarazos euploides (21,22). La PAAP-A es una proteasa que se secreta en la placenta específicamente en las células del sincitiotrofoblasto, luego se transporta a la circulación sanguínea materna y la concentración incrementa a medida que transcurre el tiempo de embarazo (13).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…There was no agreement on the relationship between serum free β-hCG levels and adverse pregnancy outcomes (APO). Ozdemir et al [ 7 ] reported correlations of the levels of the first- and second-trimester serum markers plasma protein-A (PAPP-A) and alpha-fetoprotein (AFP) with intrauterine growth restriction (IUGR) and macrosomia. In the absence of medically-indicated risk factors for premature delivery, the elevated serum free β-hCG levels of first- and second-trimester pregnant women are associated with a reduced likelihood of spontaneous preterm birth [ 8 ].…”
Section: Introductionmentioning
confidence: 99%